Wedding crashers = Die Hochzeits-Crasher - Kent, Rolfe 1963-; Faber, Steve; Fisher, Bob 1961- (New Line Productions, 2005)
John and Jeremy are single guys in their mid-30s who mediate divorces in D.C. Their summer social life consists of wedding crashing in order to meet young women for a one-night stand. As John thinks about growing up, Jeremy convinces him to go to one more wedding, this one is for the daughter of the Treasury Secretary. Each catches the eye of a bridesmaid, who happen to be daughters of the host. Jeremy quickly scores with Gloria, who proves to be a psycho clinger. John, on the other hand, wants real romance with Claire, but she has a boyfriend. Now John needs to convince Jeremy to stick around long enough so he can woo Claire. John has one more problem to deal with - telling Claire the truth about himself before someone else does
Originally released as a motion picture in 2005
Special features: optional commentary with director David Dobkin; optional commentary with Owen Wilson & Vince Vaughn; deleted scenes; "The rules" featurette; "The rules of wedding crashing"; teaser trailer; theatrical trailer
Keywords: Filmkomödie; Bachelors / Washington (D.C.) / Drama; Weddings / Washington (D.C.) / Drama; Man-woman relationships / Drama; Hombres / Washington (D.C.) / Teatro; Bodas / Washington (D.C.) / Teatro; Bachelors; Man-woman relationships; Weddings; Washington (D.C.); Videodiscs; Feature films; Video recordings for the hearing impaired; Comedy films; Drama; Fiction films; Comedy / Feature; Romance / Feature; Film; DVD-Video